2014
DOI: 10.1111/bjet.12218
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of virtual communications in communities of inquiry in higher education: Phases, evolution and participants' satisfaction

Abstract: This study investigates the phases of development of synchronous and asynchronous virtual communication produced in a community of inquiry (CoI) by analyzing the internal structure of each intervention in the forum and each chat session to determine the evolution of their social, cognitive, and teaching character. It also analyzes the participating higher education students' satisfaction with the activities, with the professors' actions, and with themselves. We use a mixed methodology that includes content ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…First, this study has shown that in an online context, there are certain group behaviors that are not recorded through discussion forums. This often occurs during the resolution phase, so it will be appropriate in future studies to include other technological tools to facilitate collaborative resolution of the task and to explore relevant learning outcomes of the resolution phase (e.g., Gutiérrez-Santiuste & Gallego-Arrufat, 2014). To do this, it seems appropriate to use analytics learning (e.g., Agudo-Peregrina, Iglesias-Pradas, Conde-González, & Hernández-García, 2014; Siemens et al., 2011).…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…First, this study has shown that in an online context, there are certain group behaviors that are not recorded through discussion forums. This often occurs during the resolution phase, so it will be appropriate in future studies to include other technological tools to facilitate collaborative resolution of the task and to explore relevant learning outcomes of the resolution phase (e.g., Gutiérrez-Santiuste & Gallego-Arrufat, 2014). To do this, it seems appropriate to use analytics learning (e.g., Agudo-Peregrina, Iglesias-Pradas, Conde-González, & Hernández-García, 2014; Siemens et al., 2011).…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…These matters are not merely concerns for theorists, but have influence and consequences for practice in higher education (HE). Many researchers in online higher education have been striving to implement constructivist instructional strategies, aiming to increase both asynchronous and synchronous communications among distance learners (e.g., Gutierrez-Santiuste and Gallego-Arrufat 2015;Ruey 2010;Smyth 2011). Do such initiatives serve students of the type indicated above?…”
Section: Introductionmentioning
confidence: 99%
“…In almost two and a half decades, the community of inquiry (CoI) framework has contributed to the monitoring of content analysis-particularly texts from forums and board comments-in a variety of asynchronous text-based environments [1][2][3][4][5][6] as well as in hybrid learning [7][8][9][10], both in university education and lifelong learning perspectives [11,12] and in association with a large diversity of tools and media [13][14][15] including the metaverse [9]. The framework was designed and tested at the Athabasca University (Canada) by Garrison, Anderson, and Archer [16], and has been increasing in popularity and scope following the leading trends of topics such as online education and e-learning.…”
Section: Introductionmentioning
confidence: 99%